Functional proteomic analysis of crossbred (Holstein Friesian × Sahiwal) bull spermatozoa. (7th February 2018) - Singh, R; Sengar, GS; Singh, U; Deb, R; Junghare, V; Hazra, S; Kumar, S; Tyagi, S; Das, AK; Raja, TV; Kumar, A
Contents: Male infertility is one of the prime concerns of dairy cattle production. The study was designed to find out differentially expressed proteins in categorized crossbred (Holstein Friesian × Sahiwal) bull semen to serve as potential biomarkers for male infertility. Frozen crossbred bull semen with satisfactory phenotypic records were defined as "good" and "poor" based on their fertility rates. A total of 1, 547 proteins were detected in bull spermatozoa using liquid chromatography–mass spectrometer (LC‐MS/MS) analysis. Results revealed that 558 (36.1%) and 653 (42.2%) proteins were expressed to good and poor quality bull spermatozoa, respectively. A total of 336 proteins (21.7%) were reported to be unique for both good and poor quality bull semen, and among the common proteins, 224 (66.7%) and 112 (33.3%) were up‐ and downregulated in good and poor quality categorized bull semen, respectively. Gene Ontology analysis of global proteomes identified different signalling pathways, and most of them were related to cellular motility, immune systems as well as cellular metabolisms. The distinctive presence of some of the proteins may provide an insight into the molecular mechanistic role played by these proteins in crossbred bull infertility.